Визначення кількості запасних елементів технічних систем - Tynynyka, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
One way to increase the level of reliability is to create sets of spare parts, units, devices to be efficiently replaced in the failed system. System availability ratio is very important for consumers. It depends on the ability to quickly replace a failed component. In order for this system to support function at the proper level, effective management of these spare parts reserve is required. Therefore, acquisition of spare parts is rightly considered as a particular problem of the theory of inventory management, the solution of which is important for ensuring service continuity of a system and, in a number of cases, for achieving the required safety.The unpredictability of failure of equipment and its parts has a great impact on this problem. One way to reduce the level of unpredictability is to maintain a sufficient number of spare parts, which leads to an increase in the cost of inventory. A cheaper way is to estimate the necessary spare parts using one of the available forecasting models.Because of this unpredictability, the nature of the demand for spare parts is stochastic, thus the models that establish an unchanged quantity of spare parts for the entire life cycle of the product only depending on the number of equipment in operation do not always provide satisfactory estimates. For this reason, it is preferable to use the models dealing with the estimation of the required number of spare parts based on such parameters as reliability of spare parts, complexity and quality of service, life expectancy, intensity of operation, maintenance costs, etc.Based on the analysis of reliability and failure rate of technical systems, the required number of spare parts is estimated in this article at the time of the expected failure or when reliability falls below a predetermined level. With the help of the obtained formula, calculations can be made for single sets of spare parts for repair, maintenance and adjustment.